2015
DOI: 10.1149/2.0801602jes
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Ni-Y2O3-ZrO2Hydrogen Electrode for Water Electrolysis Reactions in Solid Oxide Electrolysis Cells

Abstract: Ni-Y 2 O 3 stabilized ZrO 2 (Ni-YSZ) cermet is the most commonly used hydrogen electrode for hydrogen oxidation reaction (HOR) under solid oxide fuel cell (SOFC) mode and water reduction reaction (WRR) under solid oxide electrolysis cell (SOEC) mode. Here we studied the electrocatalytic activity of Ni-YSZ electrodes as a function of Ni content, water concentration and dc bias for WRR and HOR under SOEC and SOFC modes, respectively. The activity of Ni-YSZ cermet increases significantly with the increase of YSZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…The difference between the high-frequency and lowfrequency intercepts on the real axis corresponds to the polarization resistance, which is composed of several overlapping suppressed arcs reecting the physical and/or chemical processes associated with the hydrogen oxidation reaction (HOR) at the anode side and the oxygen reduction reaction (ORR) at the cathode side. 29 The polarization resistances of the cell were 0.74, 0.36, and 0.26 U cm 2 at 450, 500 and 550 C, respectively. In our previous study, we found that the Ni foam-NCAL electrode had very good ORR and HOR catalytic activities.…”
Section: Methodsmentioning
confidence: 92%
“…The difference between the high-frequency and lowfrequency intercepts on the real axis corresponds to the polarization resistance, which is composed of several overlapping suppressed arcs reecting the physical and/or chemical processes associated with the hydrogen oxidation reaction (HOR) at the anode side and the oxygen reduction reaction (ORR) at the cathode side. 29 The polarization resistances of the cell were 0.74, 0.36, and 0.26 U cm 2 at 450, 500 and 550 C, respectively. In our previous study, we found that the Ni foam-NCAL electrode had very good ORR and HOR catalytic activities.…”
Section: Methodsmentioning
confidence: 92%
“…SoA Ni-YSZ SOC fuel electrodes could be found ranging from 1.01 eV and up to 1.47 eV for the hydrogen-water reaction, depending on the fabrication method, steam content and test conditions [23][24][26][27][28]. In table 3 one can observe similarities between the change in activation energy with atmosphere, between the nickel cermet and the nickel infiltrated samples.…”
Section: Temperature Dependencementioning
confidence: 90%
“…The fuel cell performance decreases with the increase in the concentration of H 2 O and in particular CO 2 , while the electrolysis performance is enhanced with increasing the concentration of CO 2 and in particular H 2 O, consistent with previous studies. 53 This implies the type of reactant and its concentration have a dramatic effect on the cell performance. Under 50% H 2 O/50% H 2 and 50% CO 2 /50% H 2 , the cell voltage was 1.05 and 1.10 V at a current density of 0.5 A cm À2 , respectively, and increased to 1.31 and 1.61 V at a current density of 1.5 A cm À2 , respectively.…”
Section: Performance and Stability Of Directly Assembled Esb-lsm Cathmentioning
confidence: 99%